2017
DOI: 10.4236/ajps.2017.88130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a <i>Brassica napus</i> Auxin-Repressed Gene Induced by Flea Beetle Damage and <i>Sclerotinia sclerotiorum</i> Infection

Abstract: Biotic stresses negatively affect canola growth and production. Flea beetle damage and Sclerotinia sclerotiorum (S. sclerotiorum) infection are two of the worst biotic stresses for canola. Auxin Repressed Proteins (ARPs) responsive to several abiotic stresses have been reported. However, information about ARPs induced by Flea beetle damage and S. sclerotiorum infection, their roles in biotic stress tolerance are still lacking in canola. ESTs for an Auxin Repressed Protein 1 (BnARP1) were highly represented (ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Evidence has emerged for ARP family members as IDPs. ARP genes are responsive to hormones involved in responses to biotic stress, such as salicylic acid (SA) and methyl jasmonate (MeJA), as well as to hormones that regulate plant growth and development, including auxins [72,73,74]. Calreticulin (CALR) is well recognized as a Ca 2+ -binding protein molecular chaperone that assists the folding of newly synthesized glycoproteins and modulates the Ca 2+ homeostasis in the endoplasmic reticulum (ER) lumen [75].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has emerged for ARP family members as IDPs. ARP genes are responsive to hormones involved in responses to biotic stress, such as salicylic acid (SA) and methyl jasmonate (MeJA), as well as to hormones that regulate plant growth and development, including auxins [72,73,74]. Calreticulin (CALR) is well recognized as a Ca 2+ -binding protein molecular chaperone that assists the folding of newly synthesized glycoproteins and modulates the Ca 2+ homeostasis in the endoplasmic reticulum (ER) lumen [75].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, PpARP1 and PpARP2 genes are induced by 0.2mM of IAA in Pyrus pyrifolia (Shi et al, 2013). In Brassica napus, auxin 2,4-Dichlorophenoxyacetic acid strongly induces the accumulation of BnARP1 transcripts after 2 hours of treatment in transgenic lines of Arabidopsis overexpressing BnARP1 (Wu et al, 2017).…”
Section: A N U S C R I P Tmentioning
confidence: 96%
“…Likewise in our previous transcriptomics study with the same NILs, we observed the downregulation of all the disease‐resistance genes in the tolerant isolines when subjected to DS (Nouraei et al., 2022). Although several ARPs responsive to various abiotic stresses have been reported, their function in stress adaptation is less well known (L. Wu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Proteins play an essential role in the plant's phenotype by direct involvement in cell structure and metabolism (Kosová et al., 2018). Because proteins are involved in plant stress responses, proteomic studies can lead to an understanding of the possible relationships between protein changes and plant stress tolerance (S. Wu et al, 2017). Near‐isogenic lines (NILs) are lines with identical genetic backgrounds except for a few specific locations that are used to minimize genetic background effects such as epistatic interactions (Wang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%